IMPACTUL SINERGETIC ASUPRA CREĂRII DE VALOARE ÎN FUZIUNI ȘI ACHIZIȚII - Ulian, Ecaterina (CEP USM, 2024)
In this paper the author has made a critical analysis of the impact of synergies on value creation in the process of business growth through mergers and acquisitions. Qualitative analysis methods were applied in the research, such as the monographic method, comparison, synthesis. The research carried out allowed to conclude that it is not the synergies that create value, but their sources. The process of evaluating the synergistic eﬀect in value creation is complex, and the results obtained must be considered with caution by decision-makers, considering the asym-metry of information from both the position of the acquiring company and the target company.
THE SYNERGIC IMPACT ON VALUE CREATION IN M&A
Keywords: fuziuni și achiziții; performanță; efect sinergetic